1989
DOI: 10.1099/0022-1317-70-7-1725
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and Polypeptide Structure of Turkey Enteric Coronaviruses as Defined by Monoclonal Antibodies

Abstract: SUMMARYTwenty-nine hybridoma cell lines, producing monoclonal antibodies (MAbs) to the Minnesota strain of turkey enteric coronavirus (TCV), have been established by fusion of Sp2/0 myeloma cells with spleen cells from BALB/c mice immunized with purified preparations of the egg-adapted or tissue culture-adapted virus. The hybridomas produced mainly IgG2a or IgG1 antibodies. Western immunoblotting experiments with purified virus, and immunoprecipitation tests with [35S]methionine-labelled infected cell extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…5,7 Both viruses possess an hemagglutinating activity that has been associated to a 140-kD envelope glycoprotein (a disulfide-linked dimer) and additional small granular surface projections located near the base of the typical large bulbous peplomers of the coronavirions. 4,6 Both viruses are also antigenically related to the porcine HEV and human HCV-OC43 coronaviruses, 2 other viruses that belong to the subgroup of mammalian hemagglutinating coronaviruses. 26 Previous studies have demonstrated that these viruses all share antigenic determinants located on their homologous structural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Both viruses possess an hemagglutinating activity that has been associated to a 140-kD envelope glycoprotein (a disulfide-linked dimer) and additional small granular surface projections located near the base of the typical large bulbous peplomers of the coronavirions. 4,6 Both viruses are also antigenically related to the porcine HEV and human HCV-OC43 coronaviruses, 2 other viruses that belong to the subgroup of mammalian hemagglutinating coronaviruses. 26 Previous studies have demonstrated that these viruses all share antigenic determinants located on their homologous structural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of specific amino acid residues for HEV strains, in view of their virulence for pigs and their respiratory and neurological tropism, is difficult to interpret, considering that they are apparently distributed randomly among the previously mentioned proteins, except for the S protein. The S1 portion of the envelope-associated S glycoprotein is known to carry major antigenic determinants of coronaviruses that trigger the host immune response to induce the production of virus-neutralizing (VN) antibodies (Dea & Tijssen, 1989 ;Deregt & Babiuk, 1987 ;Vautherot et al, 1992). Consequently, sequence differences in S1 are thought to be responsible for many of the antigenic differences between coronaviruses .…”
Section: Cebdmentioning
confidence: 99%
“…The HE is associated with granular projections located near the base of the typical large bulbous peplomers and displays haemagglutinating (HA), acetylesterase (AE) or receptor-destroying enzyme (RDE) activities (Parker et al, 1990a, b ;Vlasak et al, 1988). The S and HE glycoproteins both possess antigenic determinants that trigger the immune response for the production of antibodies that neutralize virus infectivity and inhibit HA activity (Dea & Tijssen, 1989 ;Deregt & Babiuk, 1987 ;Michaud & Dea, 1993 ;Vautherot et al, 1992). Except for HCoV-OC43, BCoV and TCoV, these viruses do not seem to cross-react by seroneutralization or haemagglutination inhibition, but they all share common antigenic determinants on their structural proteins, as demonstrated by indirect immunofluorescence, Western blotting and immunoprecipitation assays (Dea & Tijssen, 1989).…”
mentioning
confidence: 99%
See 2 more Smart Citations